Asas Kemanusiaan Versus Kedaulatan Negara: Dilema Perlindungan Hukum Bagi Pengungsi di Perbatasan Indonesia - Setyardi, Untung (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This article examines the dilemma between humanitarian principles and state sovereignty in the context of legal protection for refugees entering Indonesia's border regions. As a non-signatory to the 1951 Refugee Convention and the 1967 Protocol, Indonesia holds no formal international legal obligations toward refugees, yet it frequently serves as a transit country for asylum seekers from conflict zones such as Myanmar, Afghanistan, and Sri Lanka. This study employs a normative juridical method, combining legislative analysis with case studies, particularly focusing on the treatment of Rohingya refugees in the coastal areas of Aceh. Findings indicate that although the non-refoulement principle is universally recognized and reflected in Presidential Regulation No. 125 of 2016, its implementation remains dependent on national political dynamics and local institutional capacity. The tension between human rights protection and sovereign control is evident in Indonesia’s often inconsistent and ad hoc responses to refugee arrivals. The article concludes that a reconstruction of national legal policy is essential to ensure minimum protection in accordance with international humanitarian norms while preserving the integrity of state sovereignty.